Brendan Buckley's universe and everything in it - Frazier, Sundee Tucker, 1968- (New York : Yearling, 2008)
Brendan Buckley, a biracial ten-year-old, applies his scientific problem-solving ability and newfound interest in rocks and minerals to connect with his white grandfather, the president of Puyallup Rock Club, and to learn why he and Brendan's mother are estranged.
"A Yearling book."
4.0
3-6
Keywords: Grandfathers -- Juvenile fiction; Racially mixed people -- Juvenile fiction; Minerals -- Collection and preservation -- Juvenile fiction; Rocks -- Collection and preservation -- Juvenile fiction; Tae kwon do -- Juvenile fiction; Family -- Washington (State) -- Juvenile fiction; Puyallup (Wash.) -- Juvenile fiction; Grandfathers -- Fiction; Racially mixed people -- Fiction; Minerals -- Collection and preservation -- Fiction; Rocks -- Collection and preservation -- Fiction; Tae kwon do -- Fiction; Family life -- Fiction; Puyallup (Wash.) -- Fiction; Grandfathers -- Fiction; Racially mixed people -- Fiction; Minerals -- Collection and preservation -- Fiction; Rocks -- Collection and preservation -- Fiction; Karate -- Fiction; Family life -- Washington (State) -- Fiction; Puyallup (Wash.) -- Fiction